Penyuluhan Tentang Siklus Menstruasi dan Faktor Yang Mempengaruhi Siklus Mestruasi Pada Wus Di Lembaga Permasyarakatan Kota Padangsidimpuan - nasution, izmi fadhilah; Nasution, Dina Rahmi solihad; Hasibuan, Elmi Sariani (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
The menstrual cycle is the time from the first day of menstruation until the next menstrual period arrives, with a normal range of 21-35 days. One of the factors that influences the menstrual cycle is anxiety. The aim of this activity is to discuss menstruation and the menstrual cycle. The aim of this community service is so that WUS in Padangsidimpuan City community institutions understand how to fulfill the health of their reproductive organs. Women can understand what is actually happening to their bodies and then look for efforts to protect themselves or alleviate the disorders they are experiencing. If you often experience problems related to menstruation, you should immediately consult a specialist doctor, so that you can diagnose as early as possible what is causing the menstrual problem or disorder. The activity method that will be carried out in this community service is education/counseling. This activity was carried out at the Padangsidimpuan City Correctional Institution. The results of this counseling activity were continued by providing an evaluation to the participants, namely questions and answers regarding menstrual material and the menstrual cycle, participants were able to answer and explain well the questions asked by the instructor/presenter. The activity went well and the participants who took part in the activity looked enthusiastic in participating in the activity. Keywords: anxiety level, menstrual cycle